AN ANALYSIS OF SILENT CONSONANTS IN THE 2ND SEMESTER STUDENTS’ PRONUNCIATION - Rosemarie, Brigitta; Veniranda, Yohana (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
This research aims to analyze the mispronounced words with silent consonants in the 2nd semester students’ pronunciation and to analyze the difficulties that the students face in pronouncing words with a silent consonant. This is a survey research. The researcher used tests and interviews as the instruments in gathering data. The respondents are the 2nd semester students of PBI Sanata Dharma University of the academic year 2020/2021.The results showed that there are 3 silent consonants that are not supposed to be pronounced but were pronounced by the 2nd semester students. Those are silent /l/, /s/ and /b/. The reasons are because of the different language accents, the comprehension of vocabularies, and the inconsistency in English pronunciation. The researcher also collected some additional information about the students’ awareness of pronunciation, their familiarity with silent consonants, and their understanding of phonetic transcription. The implication and suggestions are for English language learners, teachers and lecturers, and future researchers to develop the teaching-learning method of pronunciation.